Computational Fluid Dynamics study of element type and turbulence model impact on a flow over a spacer grid using Simcenter STAR-CCM+ (Brazilian Journal of Radiation Sciences (BJRS), 2025)
Abstract: This study presents a numerical investigation into the impact of various mesh element types on water flow results through a representative spacer grid, utilizing Computational Fluid Dynamics (CFD). The study evaluates the variations of the k−ϵ turbulence model available in Simcenter STAR-CCM+ across different mesh types. Three predominant cell types were employed: cartesian, polyhedral, and tetrahedral, alongside three k−ϵ models: Standard Two-layer (STL), Realizable Two-layer (RTL), and Elliptic Blending (EB). The analysis was conducted using a PWR vane-type spacer grid arranged in a 2x2 configuration. The findings demonstrated a strong correlation with experimental data available in the literature. However, the cartesian and tetrahedral meshes attenuated the velocity profiles post-spacer grid. The polyhedral mesh, in conjunction with the RTL and EB k−ϵ models, yielded results more closely aligned with the experimental data. Regarding Secondary Flow (SF), the results indicated a consistent trend of decreasing intensity downstream of the spacer grid. The Polyhedral EB and RTL models exhibited behavior most consistent with the experimental results.